A redox proteomic investigation of oxidative stress caused by benzoylecgonine in the freshwater bivalve Dreissena polymorpha. Issue 8 (19th September 2012) - Pedriali, Alessandra; Riva, Consuelo; Parolini, Marco; Cristoni, Simone; Sheehan, David; Binelli, Andrea
<x xml:space="preserve">Abstract</x> Drugs of abuse and their human metabolites have been recently recognized as emerging environmental contaminants. Notwithstanding the fact that these kinds of compounds share some features with pharmaceuticals, their ecotoxicology has not yet been extensively investigated, although some of their characteristics may potentially threaten aquatic ecosystems. One of the most abundant drugs found in rivers and wastewaters is benzoylecgonine (BE), the main metabolite of cocaine. We applied a redox proteomics approach to evaluate changes in the proteome of Dreissena polymorpha exposed to two different concentrations of BE (0.5 and 1 µg/l). Exposures were performed in vivo for a period of 14 days and the effect of oxidative stress on protein thiol and carbonyl groups in mussel gills were evaluated. One‐dimensional electrophoresis did not reveal a reduction in protein thiol content but showed a significant increase of protein carbonylation at both doses tested. Then, protein profiling using two‐dimensional gel electrophoresis was performed with subsequent matrix assisted laser desorption/ionization time‐of‐flight (MALDI‐TOF) and TOF/TOF with LIFT technique and linear ion trap combined with orbitrap mass spectrometer (LTQ‐Orbitrap). This yielded de novo protein sequences suitable for database searching. These preliminary results and protein identifications obtained suggest that BE causes oxidative stress. Oxidative modifications were detected in differing classes of proteins such as those of the cytoskeleton, energetic metabolism and stress response. Copyright © 2012 John Wiley & Sons, Ltd.